2018
DOI: 10.1002/joc.5434
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity analysis of wind data from 213 m high Cabauw tower

Abstract: Homogeneous meteorological data are a prerequisite for reliable climatological studies. This paper investigates the homogeneity of wind data from 213 m high Cabauw tower located in The Netherlands. The wind measurements are conducted at 10, 20, 40, 80, 140 and 200 m above ground. The analysed data cover the period from February 1986 to January 1997 and from April 2000 to December 2015. This study presents the first homogeneity analysis of wind data from a tall meteorological mast. Homogeneities of wind speed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The site is flat in all directions within ;20 km from the tower. The land use within ;400 m around the tower is open pasture (Petrovic ´et al 2018;van den Berg 2008;Verkaik and Holtslag 2007).…”
Section: A Wind Measurementsmentioning
confidence: 99%
“…The site is flat in all directions within ;20 km from the tower. The land use within ;400 m around the tower is open pasture (Petrovic ´et al 2018;van den Berg 2008;Verkaik and Holtslag 2007).…”
Section: A Wind Measurementsmentioning
confidence: 99%
“…Similarly Petrović et al . () demonstrated that the measurement of wind speed at the KNMI Cabauw tower (near Lopik, The Netherlands) was influenced by the extension of the built‐up city area around the tower.…”
Section: Discussionmentioning
confidence: 99%
“…Terrain and surface type significantly impact the intensity and trajectory of typhoons, subsequently influencing the extreme wind speeds and duration experienced by station wind towers [30]. Examining the path of Typhoon "Lijima," it traversed primarily through Zhejiang, Jiangsu, and Shandong provinces.…”
Section: Influence Of the Cushion On The Wind Speed Of The Towermentioning
confidence: 99%